2023
DOI: 10.1029/2022gl101658
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Urban Signatures in Rainfall Anomalies Explained by Pre‐Storm Environment Contrast

Abstract: Understanding urban impacts on hydrometeorological processes is becoming an emergent issue under the context of soaring urban population globally (UNPD, 2019). This is accompanied by ample evidence of elevated extreme rainfall and flood hazards under a changing climate, with urban areas most vulnerable (IPCC, 2021). Empirical and modeling analyses reveal notable urban-induced rainfall anomalies over a collection of worldwide cities, including the pioneering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…Therefore, precipitation tends to occur over the city center. However, under higher wind speeds, the UHI intensity is smaller compared to low wind speeds (e.g., Dou et al., 2015; Ngarambe et al., 2021; Shen & Yang, 2023) reported by multiple studies and the urban‐rural circulation is weaker. The background wind dominates the flow pattern around the city, which corresponds to the plume regime.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Therefore, precipitation tends to occur over the city center. However, under higher wind speeds, the UHI intensity is smaller compared to low wind speeds (e.g., Dou et al., 2015; Ngarambe et al., 2021; Shen & Yang, 2023) reported by multiple studies and the urban‐rural circulation is weaker. The background wind dominates the flow pattern around the city, which corresponds to the plume regime.…”
Section: Resultsmentioning
confidence: 98%
“…This serves to average out the effects of other factors on the spatial distribution of precipitation, which are unaccounted for in the analysis, such as the magnitude of surface urban heat island and pre‐storm environments Dou et al. (2015) and Shen and Yang (2023). Thus, the average of Φ( r ) across all the cities is useful to understand the overall trend due to the interaction between urban structures and specific meteorological conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms behind urban modification of extreme precipitation are quite complex and elusive under some weather conditions. A recent study analyzed the urbanization effect on rainfall in Nanjing under different urban temperature anomalies and background circulation conditions during pre-storm periods (Shen & Yang, 2023). It found that the location where rainfall intensified depends on the strength of synoptic forcing when the UHI is weak.…”
Section: Discussionmentioning
confidence: 99%